Analysis of Factors Not Achieving Fasting Blood Glucose Levels of Diabetes Mellitus Patients at the Singgani Health Center Palu City - Nurul Adha; Siti zahra; Tisya Rizky Diahpati; Afifah Qanita; Nadia Vega; Junaldi Akbar; Ismail; Amelia Rumi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Diabetes Mellitus is still a serious health problem worldwide, especially in Indonesia. Due to its persistent nature and increasing prevalence, it appears that efforts to control this disease still face many challenges in its implementation in the community. Several risk factors play a role in the development of this disease. These include family history of diabetes, environmental influences, age, obesity, ethnicity, comorbidities, medication, occupation, unhealthy diet, and physical inactivity. Objective: The purpose of this study was to determine the factors of not achieving fasting blood glucose levels in patients with diabetes mellitus at the Singgani Health Center in Palu City. Method: This study used a cross-sectional design in patients with diabetes mellitus at the Singgani health center in Palu City, data collection was carried out using non-probability sampling techniques with purposive sampling techniques, with a total sample of 100. Data were obtained from the results of patient medical records, data analysis using descriptive analysis, namely the analysis method used to describe the characteristics of the research subjects and the character of blood glucose levels, then analyzed using SPSS, namely to see the analysis of factors not achieving fasting blood glucose levels statistically tested using Chi-Square. Result: The results of the study were that most patients were in the category of unattainable fasting blood glucose levels, totaling 87 patients ? 110 mg/dl out of a total of 100 samples. As well as being influenced by sociodemographic characteristic factors, namely in employment status, namely in the group of patients not working in the category of fasting blood glucose not reached, totaling 62 patients, with an Odds Ratio of 2.32 with a significance value of p = 0.02. Conclusion: The employment status of 62 patients in the non-working group had a 2.32 times risk of not achieving fasting blood glucose levels.